Implementation of Asean Regional Forum (ARF) on Trafficking in Persons in The Asia Pacific Area - Rafitri, Liftihar (Jurnal Diplomasi Pertahanan, 2021)
The case of human trafficking is not only a threat to human security but also national and international security. The development of human trafficking cases increasing the awareness that security is one of the factors that can affect the prosperity and stability of a country and region. So that countries are encouraged to cooperate, especially regional cooperation through the ASEAN Regional Forum. The results of this study indicate that the implementation of ARF in handling human trafficking cases in Southeast Asia is still lacking. This can be seen in the lack of projects that have been implemented and regular meetings to discuss the handling of cases of human trafficking in Southeast Asia. The research method used in this study is a qualitative research method with data collection techniques in the form of literature studies obtained from books, journals, news, and other related literature.Keywords: ASEAN Regional Forum (ARF), Human Security, Human Trafficking, Regional Cooperation.